2022
DOI: 10.3390/bioengineering9060249
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Additive Manufacturing Studies for Producing Customized Ankle-Foot Orthoses

Abstract: Ankle-foot orthoses (AFO) are prescribed to improve the patient’s quality of life. Supporting weak muscles or restraining spastic muscles leads to smoother and more stable locomotion. Commonly, AFO are made using thermoplastic vacuum forming, which requires a long time for production and has limited design options. Additive manufacturing (AM) can solve this problem, leading to a faster and cheaper solution. This review aimed to investigate what is the state-of-art using AM for AFO. Evaluating the used manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Our sample of 29 subjects (58 feet/ankles) is broader than most samples studied in previous surveys (30 subjects in Labs and al [40], 20 limbs for the validation of the Perometer→ [10]; Tierney et al [ 27] reported on 20 leg segments). Furthermore, the validation of our scanner was carried out within a population in which very varied volumes were observed, ranging from 537. ensured that differences between the two methods were normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample of 29 subjects (58 feet/ankles) is broader than most samples studied in previous surveys (30 subjects in Labs and al [40], 20 limbs for the validation of the Perometer→ [10]; Tierney et al [ 27] reported on 20 leg segments). Furthermore, the validation of our scanner was carried out within a population in which very varied volumes were observed, ranging from 537. ensured that differences between the two methods were normal.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the exact volume, the difference in volume between the genders, the variation in volume over the course of a day or sports activities would be beneficial for the manufacture of shoes [10,11,12,13]. Once again, the medical field could improve the management of footwear for different foot morphotypes or conditions such as Cavo varus feet, progressive collapsing foot deformity or hallux valgus [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This can take from 2 days to many weeks, depending on the amount of postprocessing required. [ 15,79,80 ] Additionally, the entire manufacturing process must be repeated if the AFO is destroyed or the patient's condition changes. [ 81 ]…”
Section: Introductionmentioning
confidence: 99%
“…Human walking is typically conceptualized as the repetitive movement of the limbs and is a distinctive feature of human locomotion, with each individual possessing a distinct style of walking [ 1 ]. Humans with conditions that affect the hip, knee, or ankle bones, nerves, muscles, or joints may have difficulties in walking.…”
Section: Introductionmentioning
confidence: 99%